Analisis Keselamatan dan Risiko pada Pekerjaan Pengembangan Kilang Minyak dan Petrokimia dengan Metode JSA - Saputra, Nando; Kisanjani, Alex; Andivas, Marulan; Angga, Angga (SURYA TEKNIKA, 2024)
Working at heights poses serious risks, including accidents and fatal injuries.Workers may also experience psychological stress and the physical and mental health impacts due to environmental conditions or psychological pressure. Restricted movement, difficulties in evacuation, and the use of safety equipment are also issues that require the implementation of effective safety measures and adequate training. This research aims to identify hazards through Job Safety Analysis (JSA) using descriptive analytical methods and field observations. The collected data is used as a basis to formulate control measures to prevent accidents or minimize risks. The results of the analysis of those activities serve as safety guidelines/procedures for all work activities.